(untitled) (Research, Society and Development, 2022)
Objective: To compare the clinical outcomes of patients infected with SARS-CoV-2 variants with patients infected with the original strain. Methods: This is a case control study comparing cases of COVID-19 patients infected with SARS-CoV-2 variants of concern identified by genomic sequencing, with a control group of 62 patients randomly selected from a COVID-19 database of patients diagnosed prior to the emergence of these variants. Findings: In the 40 patients infected with variants, the predominant (52.5%) was P.1 variant. The variant group presented more arthralgia (p=0.015), hyporexia (p=0.006), nausea/vomiting (p=0.048), and mental confusion (p=0.029), the last not identified in the control group. There were no significant differences in comorbidities or demographic data between the groups. Severe disease, according to the WHO Clinical Progression Scale, was identified only in those infected with the variants, as well as high-flow oxygen therapy and ICU admission (p=0.05). The two deaths reported in the study were in patients infected with the variants. Conclusions: The worst outcomes were observed in the group infected with SARS-CoV-2 variants, although no significant differences in comorbidities or demographics date were observed between the groups.